Transcriptional profiling of Vibrio cholerae O1 following exposure to human anti- lipopolysaccharide monoclonal antibodies. Issue 4 (26th June 2020) - Baranova, Danielle E; Willsey, Graham G; Levinson, Kara J; Smith, Carol; Wade, Joseph; Mantis, Nicholas J
ABSTRACT: Following an episode of cholera, a rapidly dehydrating, watery diarrhea caused by the Gram-negative bacterium, Vibrio cholerae O1, humans mount a robust anti-lipopolysaccharide (LPS) antibody response that is associated with immunity to subsequent re-infection. In neonatal mouse and rabbit models of cholera, passively administered anti-LPS polyclonal and monoclonal (MAb) antibodies reduce V. cholerae colonization of the intestinal epithelia by inhibiting bacterial motility and promoting vibrio agglutination. Here we demonstrate that human anti-LPS IgG MAbs also arrest V. cholerae motility and induce bacterial paralysis. A subset of those MAbs also triggered V. cholerae to secrete an extracellular matrix (ECM). To identify changes in gene expression that accompany antibody exposure and that may account for motility arrest and ECM production, we subjected V. cholerae O1 El Tor to RNA-seq analysis after treatment with ZAC-3 IgG, a high affinity MAb directed against the core/lipid A region of LPS. We identified > 160 genes whose expression was altered following ZAC-3 IgG treatment, although canonical outer membrane stress regulons were not among them. ompS ( VCA1028 ), a porin associated with virulence and indirectly regulated by ToxT, and norR ( VCA0182 ), a σ54-dependent transcription factor involved in late stages of infection, were two upregulated genes worth noting. Abstract : Vibrio cholerae alters gene expression upon encountering mucosal antibodies.